2002
DOI: 10.1002/1521-4141(200208)32:8<2274::aid-immu2274>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune responses induced by mucosal administration of lipopeptides without adjuvant

Abstract: We recently reported that parenteral injection of malaria palmitoyl‐tailed peptides without adjuvant efficiently induces B, Th and CTL responses. We now show that intranasal (IN) or sub‐lingual (SL) delivery of such lipopeptides induces strong systemic immune responses, as demonstrated by specific Th cell responses from the spleen as well as inguinal lymph nodes, and by the production ofhigh levels of serum antibodies. Overall, both types of responses were significantly higher than in parallel experiments in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 22 publications
0
81
0
Order By: Relevance
“…Identically prepared cultures were incubated with anti-CD8 MAb 53-6.7 (PharMingen) or with an isotype-matched control Ab, all at 10 g/ml. It has been previously shown that these antibodies show the expected specificities and function as expected (3,4). Cytokine analysis.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Identically prepared cultures were incubated with anti-CD8 MAb 53-6.7 (PharMingen) or with an isotype-matched control Ab, all at 10 g/ml. It has been previously shown that these antibodies show the expected specificities and function as expected (3,4). Cytokine analysis.…”
Section: Methodsmentioning
confidence: 86%
“…Twelve days after the second immunization, spleen and inguinal lymph nodes were removed and placed in ice-cold serumfree HL-1 medium supplemented with 15 mM HEPES, 5 ϫ 10 Ϫ5 M ␤-mercaptoethanol, 2 mM glutamine, 50 U of penicillin, and 50 g of streptomycin (GIBCO-BRL, Grand Island, N.Y.) (CM) (3,4). The cells were cultured in 96-well plates at 5 ϫ 10 5 cells/well in CM, with recall or control peptide at a 30-, 10-, 3-, 1-, or 0.3-g/ml concentration, as previously described (3,4 and the T-cell mitogen concanavalin A (Sigma, St. Louis, Mo.) were used as negative and positive controls, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although the high degree of HLA polymorphism is often pointed to as a major hindrance to the use of epitope-based vaccines, this constraint can be dealt with through the inclusion of multiple supertype-restricted epitopes recognized in the context of diverse related HLA alleles and by designing mixtures of peptide-based vaccines with higher epitope densities (2,3,7,8,11,24,25). Broad population coverage can be established providing that epitopes corresponding to multiple HLA supertype families are incorporated into the vaccine.…”
Section: Cd8mentioning
confidence: 99%
“…The sublingual (s.l.) 3 route has been used for many years to deliver low-molecular-weight drugs, including small immunogenic peptides (5,6). The s.l.…”
mentioning
confidence: 99%